Proceedings of the 11th International Symposium on Computer Science in Sport (IACSS 2017) (Advances in Intelligent Systems and Computing,, 2018)
This book provides an overview of current research in the fascinating, interdisciplinary field of computer science and sports. It includes papers from the 11th International Symposium on Computer Science in Sport (IACSS 2017), which took place in Constance, Germany, on September 6-9, 2017. The papers represent the state of the art in utilizing the latest developments in computer science to support coaches and athletes. The book covers a broad range of topics, reflecting the diversity of the field. It presents three categories of papers: those on concepts in informatics like modeling, virtual reality, simulation; those describing applications of computer science in sports like running, volleyball, water polo, and football; and contributions discussing the impact of computer science in sports federations and universities. .